Psychometric properties and factorial invariance of the Farsi version of the Stress Mindset Measure - Tedadi, Yaser; Daryani, Yalda; Karsazi, Hossein (Frontiers in Psychology, 2022)
The Stress Mindset Measure consists of eight items to assess whether individuals hold a stress-is-enhancing or a stress-is-debilitating mindset. The current research is a cross-sectional study and aimed to investigate the factor structure, internal consistency reliability, and construct and convergent validity of the Farsi version of the Stress Mindset Measure (SMM). Prior to conducting the study, forward and backward translations of the SMM were performed. Using the convenience sampling method, we recruited 400 none-clinical sample (161 men and 239 women; aged 18 to 69). We utilized SPSS version 24, Amos, and Mplus 7.1 software to analyze the data. Results revealed satisfactory reliability and validity indexes for the Farsi version of the Stress Mindset Measure. The internal consistency of the Farsi version of the Stress Mindset Measure was in the excellent range (ɑ = .87). The results of the confirmatory factorial analysis revealed two factors of the Stress Mindset Measure instead of the single factor suggested by the previous studies (fitness indices for the two-factor model were RMSEA = .78, CFI = .96, and TLI = .94). Moreover, we found that the stress-is-debilitating mindset is positively associated with stress (r = .233), depression (r = .163), and anxiety (r = .197). However, this mindset has been found to have no significant relationship with cognitive strategies of emotion regulation and life satisfaction. Also, findings showed no significant correlation between the stress-is-enhancing mindsets and the other variables. The results of this study suggest that the Farsi SMM has proper psychometric properties to assess stress mindsets.